Combined inhibition of MEK and PI3K pathways overcomes acquired resistance to EGFR‐TKIs in non‐small cell lung cancer. Issue 10 (14th September 2018) - Sato, Hiroki; Yamamoto, Hiromasa; Sakaguchi, Masakiyo; Shien, Kazuhiko; Tomida, Shuta; Shien, Tadahiko; Ikeda, Hirokuni; Hatono, Minami; Torigoe, Hidejiro; Namba, Kei; Yoshioka, Takahiro; Kurihara, Eisuke; et al.
Abstract : Compensatory activation of the signal transduction pathways is one of the major obstacles for the targeted therapy of non‐small cell lung cancer (NSCLC). Herein, we present the therapeutic strategy of combined targeted therapy against the MEK and phosphoinositide‐3 kinase (PI3K) pathways for acquired resistance to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) in NSCLC. We investigated the efficacy of combined trametinib plus taselisib therapy using experimentally established EGFR‐TKI‐resistant NSCLC cell lines. The results showed that the feedback loop between MEK/ERK and PI3K/AKT pathways had developed in several resistant cell lines, which caused the resistance to single‐agent treatment with either inhibitor alone. Meanwhile, the combined therapy successfully regulated the compensatory activation of the key intracellular signals and synergistically inhibited the cell growth of those cells in vitro and in vivo. The resistance mechanisms for which the dual kinase inhibitor therapy proved effective included (MET) mesenchymal‐epithelial transition factor amplification, induction of epithelial‐to‐mesenchymal transition (EMT) and EGFR T790M mutation. In further analysis, the combination therapy induced the phosphorylation of p38 MAPK signaling, leading to the activation of apoptosis cascade. Additionally, long‐term treatment with the combination therapy induced the conversion from EMT to mesenchymal‐to‐epithelial transition in the resistant cell line harboring EMT features, restoring the sensitivity to EGFR‐TKI. In conclusion, our results indicate that the combined therapy using MEK and PI3K inhibitors is a potent therapeutic strategy for NSCLC with the acquired resistance to EGFR‐TKIs. Abstract : Effect of MEK/PI3K dual blockade was examined using EGFR‐TKI‐resistant NSCLC cells. Single‐agent therapies led to the compensatory activation of other pathways. Combination therapy inhibited the growth of resistant cells in vitro and in vivo